Manajemen Sumber Daya Manusia dalam Pendidikan Agama Islam: Konsep, Implementasi, dan Tantangan Pengembangannya - Madyan, Madyan; Mardlaatillah, Aina; Maddu, Nurmila; Anita, Anita; Yudisti, Muhammad Pran (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to examine the concept and implementation of human resource management (HRM) in Islamic Religious Education (IRE). The method used is a library research approach with descriptive-analytical techniques applied to various relevant literature sources. The findings indicate that HRM in IRE encompasses managerial functions including planning, recruitment, training, performance evaluation, and compensation, all of which are integrated with Islamic values. Effective HRM has been shown to contribute significantly to improving teacher competence, work motivation, and the quality of IRE learning. However, several challenges remain, including low professionalism among educators, limited funding, inadequate mastery of digital technology, and the suboptimal integration of Islamic values with modern management systems. This study concludes that human resource management in Islamic education must be carried out systematically, sustainably, and based on Islamic values in order to realize quality education and produce generations that are both intellectually excellent and morally virtuous.